2017
DOI: 10.1155/2017/7241281
|View full text |Cite
|
Sign up to set email alerts
|

Resource Allocation Schemes for Multiple Targets Tracking in Distributed MIMO Radar Systems

Abstract: Considering the demands of different location accuracy for multiple targets tracking, performance-driven resource allocation schemes in distributed MIMO radar system are proposed. Restricted by the tracking antenna number, location estimation meansquare error (MSE), and target priorities, an optimization problem of the minimal antenna subsets selection is modeled as a knapsack problem. Then, two operational schemes, modified fair multistart local search (MFMLS) algorithm and modified fair multistart local sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…6 indicates that the maximum number of detectable targets on the particular PMIMO radar with M = 4, N = 8, is 8. This is in agreement with the result from (33) for M = 4, for which the number of P max,PMIMO is in the range of [5,16].…”
Section: C: Phased Mimo Radarsupporting
confidence: 93%
“…6 indicates that the maximum number of detectable targets on the particular PMIMO radar with M = 4, N = 8, is 8. This is in agreement with the result from (33) for M = 4, for which the number of P max,PMIMO is in the range of [5,16].…”
Section: C: Phased Mimo Radarsupporting
confidence: 93%
“…The normalized processing time of the measurement matrix design is higher than the energy allocation method. Song, X., Zheng, N. and Bai, T [17] introduced a distributed MIMO radar system with antenna selection schemes for improving the performance of resource allocation. These antenna selection schemes are introduced for tracking the multiple targets with various location estimation MSE and priorities of the targets.…”
Section: Literature Workmentioning
confidence: 99%
“…Therefore, Bayesian Cramer Rao Lower Bound is extracted, normalized, and utilizes as the optimization criterion. To increase the system performance and resource utilization of widely separated MIMO radar, a joint resource allocation for velocity estimation problem in multi-target tracking is proposed in [23]. The authors chose one target as a key target and then examined their strategy by this target.…”
Section: -Introductionmentioning
confidence: 99%
“…For instance, in [12], range-only estimation for target tracking in MIMO radar with widely separated antennas is performed and it is not considered velocity. Whereas, in [23], velocity estimation is utilized to compute target tracking for power allocation problem in distributed MIMO radar. These are just some papers which we investigated and we concluded that joint estimation for target tracking in power allocation problem for MIMO radar with widely separated antennas is not used yet.…”
Section: -Introductionmentioning
confidence: 99%